Effect of a high and low dose of caffeine on antigen-stimulated activation of human natural killer cells after prolonged cycling - Fletcher, D. K.; Bishop, N. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
This study investigated the effect of a high and low dose of caffeine on antigen-stimulated natural killer (NK) cell (CD3- CD56+) activation after prolonged, strenuous cycling, as assessed by the early-activation molecule CD69. In a randomized crossover design, 12 healthy male endurance-trained cyclists cycled for 90 min at 70% VO2peak 60 min after ingesting either 0 (PLA), 2 (2CAF), or 6 (6CAF) mg/kg body mass of caffeine. Whole blood was stimulated with Pediacel (5 in 1) vaccine. A high dose of caffeine (6CAF) increased the number of CD3-CD56+ cells in the circulation immediately postexercise compared with PLA (p < .05). For both 2CAF and 6CAF, the geometric mean fluorescence intensity (GMFI) of CD69+ expression on unstimulated CD3-CD56+ cells was significantly higher than with PLA (both p < .05). When cells were stimulated with antigen, the GMFI of CD69 expression remained significantly higher with 2CAF than with PLA 1 hr postexercise (p < .05). Although not achieving statistical significance, 6CAF also followed a similar trend when stimulated (p = .09). There were no differences in GMFI of CD69 expression between 2CAF and 6CAF. These results suggest that a high (6 mg/kg) dose of caffeine was associated with the recruitment of NK cells into the circulation and that both a high and low (2 mg/kg) dose of caffeine increased unstimulated and antigen-stimulated NK-cell activation 1 hr after high-intensity exercise. Furthermore, there does not appear to be a dose-dependent effect of caffeine on NK-cell activation 1 hr after prolonged intensive cycling.